2022
DOI: 10.1007/s12063-022-00253-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting repurposing operations in Micro Small and Medium Enterprises during Covid-19 emergency

Abstract: Micro, Small and Medium Enterprises (MSME) sector plays a substantial role in the overall economic development and employment generation of a country. The Covid-19 pandemic has impacted adversely, and it is inevitably necessary to consider the influence of the pandemic on MSME, which will assist the policymakers in helping in the repurposing operations of the sector. Because of its size, scale of operations, and availability of financial resources, the MSMEs sector has been one of the most susceptible sectors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The FRM was created via the transitivity check, and this is the fourth step of TISM (Sreenivasan and Suresh, 2022). Table 3 contains the FRM.…”
Section: Marketing Opportunities (F7)mentioning
confidence: 99%
See 1 more Smart Citation
“…The FRM was created via the transitivity check, and this is the fourth step of TISM (Sreenivasan and Suresh, 2022). Table 3 contains the FRM.…”
Section: Marketing Opportunities (F7)mentioning
confidence: 99%
“…MICMAC involves categorization of the identified factors into four classes (Suresh et al 2021;Suresh et al 2019a;Suresh et al 2019b;Suguna et al, 2022), and it's shown in Table 5. 6 shows the ranking of the factors influencing MSMEs performance.…”
Section: Micmac Analysismentioning
confidence: 99%
“…As for supply-chain management, resilience and sustainability are key issues [30][31][32][33]. Logistics disruptions continue to affect agriculture, small and medium-sized enterprises, and cross-border supply [8,16,[34][35][36]. Recognizing the specific difficulties and corresponding management strategies is an important part of post-epidemic logistics management [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…As for supply chain management, resilience and sustainability are the primary topics [30][31][32][33] . Today, logistics disruptions continue to affect agriculture, small and medium-sized enterprises, and cross-border logistics 8,16,[34][35][36] . Recognizing specific difficulties and corresponding management strategies is an important part of post-epidemic logistics management 20,21 .…”
Section: Introductionmentioning
confidence: 99%